2005
DOI: 10.1177/0895904805276143
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Teacher Sensemaking: School Leaders and the Enactment of Reading Policy

Abstract: A growing body of research has emphasized the social processes by which teachers adapt and transform policy as they enact it in their classrooms. Yet little attention has been paid to the role of school leaders in this process. Drawing on sociological theories of sensemaking, this article investigates how principals in two California elementary schools influenced teacher learning about and enactment of changing reading policy. It argues that principals influence teachers' enactment by shaping access to policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
479
2
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(524 citation statements)
references
References 40 publications
18
479
2
15
Order By: Relevance
“…In die benadering wordt de -individuele en collectieve-betekenisgeving van de betrokken actoren centraal geplaatst in het begrijpen van implementatieprocessen (Coburn, 2001(Coburn, , 2005Fullan, 2001;Spillane, Reiser, & Reimer, 2002;Van den Berg, 2002 …”
Section: De Sociale Dimensie Van Onderwijsvernieuwingenunclassified
“…In die benadering wordt de -individuele en collectieve-betekenisgeving van de betrokken actoren centraal geplaatst in het begrijpen van implementatieprocessen (Coburn, 2001(Coburn, , 2005Fullan, 2001;Spillane, Reiser, & Reimer, 2002;Van den Berg, 2002 …”
Section: De Sociale Dimensie Van Onderwijsvernieuwingenunclassified
“…As observed by Coburn (2007), research drawing on sociological theories of sense-making provides evidence that local interpretation shapes the direction of policy implementation. It suggests that local actors in schools actively construct their understanding of policies by interpreting them through the lens of their pre-existing beliefs and practices.…”
Section: Context Of Practicementioning
confidence: 99%
“…Bowe et al (1992) have underlined that practitioners at school level interpret the policy in relation to their own understanding, experiences, histories, desires, values, purposes, means, and preferred way of working. In addition, drawing on sociological theories of sense-making, Coburn (2007) noted that research has indicated that teachers come to understand new policy ideas through the lens of their pre-existing knowledge as well as practices, often interpreting, adapting, or transforming policy messages. This is a reason why interpretation of the policy is a matter of struggle (Peters, 2003).…”
Section: Context Of Practicementioning
confidence: 99%
“…The research illuminated strategies used in the school environment that are contributing factors for how principals successfully implement their roles and take action (Coburn, 2005;Daly, Moolenaar, Bolivar, & Burke, 2010;Spillane, Parise, & Sherer, 2011). As Coburn (2005) stressed, principals need to create a collaborative, clear mission and vision focused on academic excellence in order to increase student achievement. It is important to increase efficacy by ensuring educators have a clear understanding of how to implement the standards (Coburn, 2005).…”
Section: Relevant Literaturementioning
confidence: 99%
“…As Coburn (2005) stressed, principals need to create a collaborative, clear mission and vision focused on academic excellence in order to increase student achievement. It is important to increase efficacy by ensuring educators have a clear understanding of how to implement the standards (Coburn, 2005). In addition, the definition of a principal's role and work within a school is to provide a map of the contextual information in which principals, principal preparation programs, school districts, and other principal support programs produce effective outcomes (Daly et al, 2010).…”
Section: Relevant Literaturementioning
confidence: 99%